Implementasi ERP Sumber Terbuka untuk Bisnis Ritel Kecil: Studi Kasus Optimalisasi Manajemen Inventaris di Rendy Audio - Steven; Stefanus Mauricio; Dewi Hajar (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2026)
This study focuses on integrating an inventory management system for Rendy Audio, a small retail company with only four employees that installs and customizes vehicle audio systems, using the open-source ERP Odoo. The purpose of a centralized digital system that connects inventory operations with real-time procurement and sales data is to improve order processing, inventory management, and stock visibility. Rendy Audio intends to use Odoo's Inventory module to automate manual processes, reduce stock discrepancies, and gain real-time visibility into stock levels, order statuses, and inventory locations. This study follows a four-phase methodology that includes preparation and planning, data collection and analysis, system design and prototype, and deployment including user training. The results suggest that utilizing Odoo improves customer service, reduces order processing time, and improves inventory tracking accuracy. These findings support Odoo ERP's efficacy as a scalable and reasonably priced inventory management solution tailored to the needs of small merchants.